Marie Jaëll : the magic touch, piano music by mind training - Guichard, Catherine (Algora Pub., 2004)
A biographical work about the world-renowned Alsatian piano prodigy, composer, and influential teacher who personified the passion of the Romantic Age as it met Modernism before the turn of the 20th century.